La pintura de paisaje y su relación con la formación de una identidad territorial en América - Benites Torres, Cintya Milagros (2025)
During the nineteenth century, the Romantic sensibility in the West brought landscape painting to the forefront. When it moved to the American continent, this led to the search for the local landscape to achieve the construction and affirmation of the notion of nationhood among the new American republics towards the end of the century. However, the landscape treatment within national formation varied, as each context influenced it. In the case of Peruvian painting, this process was not accomplished simultaneously with other American examples from the nineteenth century, but it happened subsequently. This article aims to explore the approach of landscape painting in the American environment and its connection to constructing a national identity linked to the territory. Consequently, it establishes an ideological continuity between the territory captured in landscape painting in the nineteenth century, which influenced Peruvian painting, and the design of a local identity throughout the twentieth century.